Response of Bajra Varieties to Nitrogen Application - Porwal, B L; Mathur, M K (Annals of Arid Zone, 2016)
From the results obtained of the experiment on comparison between ten Bajra varieties at three levels of nitrogen application, it could be concluded that for Jobner region, under rainfed condition. Hybrid Bajra-l with nitrogen dose of 40 kg N/ha could be recommended.